PRINSIP HUKUM KONTRAK DALAM LISENSI MEREK - Agung Sujatmiko (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
Trademark rights  is an exclusive right. This exclusive right covers two things that are right to use the trademark and right to give license to other people to use trademark. Therefore, one method to use other peoples trademark securely and legally is by concluding a license agreement. A license agreement is a contract which is concluded by licensor and licensee, followed by the payment of royalty,  which has to be paid by licensee to the licensor. The licensee agreement regulates rights and duties of the parties. This agreement has to be registered to the Directorat General Intellectual Property Rights (DG IPR) Department of Law and Human Rights. If it is not registered, this  agreement has no legal effects. As a contract, this agreement has to based on contract principles, such as : freedom of contract; consensualism; pacta sunt servanda; equity; profit of contract and good faith.